A Multiscale Approach for Modeling Oxygen Production by Adsorption - Pavone D.; Roesler J. (Oil & Gas Science and Technology, 2013)
Oxygen production processes using adsorbents for application to CCS technologies (Carbon Capture and Storage) offer potential cost benefits over classical cryogenics. In order to model adsorption processes an approach using three size scales has been developed. This work is being conducted in the framework of the DECARBit European research project. The first scale is at the size of the oxygen adsorption bed to be modelled as a vertical cylinder filled with pellets. Its length is 0.2 m (scale 10-1 m). The bed is homogeneous in the transversal direction so that the problem is 1D (independent variables t, x). The physics in the process include gas species (Cbk (t, x)) convection and dispersion, thermal convection and conduction (T(t, x)) and hydrodynamics (v(t, x)). The gas constituents involved are N2, 02, CO2 and H2O. The second scale is at the size of the pellets that fill the adsorber and which are assumed to be of spherical shape with a typical radius of 5 mm (scale 10-3 m). The independent variable for the pellets is the radius “rp”. At a certain height (x) down in the adsorber all the pellets are the same and are surrounded by the same gas composition but inside the pellets the concentrations may vary. The state variables for the inner part of the pellets are the gas concentrations Cpk(t, x, rp). The pellets are so small that they are assumed to have a uniform temperature. This leads to a 2D transient model for the pellets linked to the 1D transient model for the bulk. The third scale looks into the detailed structure of the pellets that are made of perovskite crystallites. The latter are assumed to be spherical. Oxygen adsorption occurs in the crystallites which have a radius of about 0.5 pm (scale 10-7 m). All the crystallites at the same radius in a pellet are supposed to behave the same and because they are spherical, the only independent variable for a crystallite located at (x, rp) is its radius “rc”. The state variables for the crystallites are then the adsorbed oxygen concentration Cc2 (t, x, rp, re). The crystallites are so small that they are assumed to have a uniform temperature. This leads to a third transient model that is 3D for the crystallite and is linked to the 2D transient model for the pellets which is itself linked to the 1D transient models for the bulk. From the larger to the lower scales, the links between the three models are the following: the bulk concentration and temperature give the boundary conditions surrounding the pellets. The pellet concentration gives the boundary conditions for the crystallites. We chose to solve this multiscale approach that requires the coupling of models of different dimensions in Comsol Multiphysics. The simulator was built to gain knowledge from laboratory experiments in order to estimate whether oxygen separation from air is realistic or not.